Phenotypic Detection of AmpC B-Lactamases in Gram Negative Bacteria (Bangladesh Journal of Medical Microbiology, 2016)
This study  was  carried  out to  detect  AmpC  f}-lactamase  producing Gram-negative  bacteria.  A total  of 374 bacterialisolates  from  primary  cultures  of wound  swab  (n:196)  and  urine (n:178)  specimens  collected  from  BSMMU  andDMCH  were investigated.  Among  the  total  374  isolates,  344 (91.98o/o) were Gram-negative  and 30  (8.027o) wereGram-positive bacteria. Majority of the  Gram-negative  bacterial  isolates  were Escherichia  coli isolated  from  160(46.520/0)  of  the  cases  followed  by  Pseudomonas  species  (74,19.79o ), Klebsiella  species (4i2,l1.23oh),  Enterobacterspecies  (28,7.49o/o)  and  Enterococcus species  (20, 5.35yo).  All  isolates  were subjected  to antimicrobial  susceptibilitytest  by Kirby-Bauer  disc diffusion  method  and  Gram-negative  lst  line-drug-resistant  isolates  were tested  for  AmpCf3-lactamase  production by disc approximation test.  Amon g 344  Gram-nrcgative  bacteria  isolated,  183(53.2%)  were1st-line-drug-resistant  of  which AmpC fJ-lactamase  was detected  in  51 (27.8  7o/o) isolates..  The highest  rate  of AmpC Blactamase  production  was observed  among  Enterobacter  spp.  (5/10, 50o/o),  followed  by  E. coli  (23174,31o/o),  Klebsiellaspp.  (7127,25.92oh),  Pseudomonas  spp.  (11145,24.44o/o),  Acinetobacter spp. (3/15,  20r/o) and  Proteus  spp. (2112,16.670 ). Among  individual  samples,AmpC  positive  strains  were  found  as  the  highest  in  isolates  from  urine  (22/69,31.8870),  closely  followed  by  in  burn  wounds (30.88%)  and surgical  wounds (17.39oh).  AmpC  f3-lactamase producingE. coli  was  found  as the  highest in burn  wounds (50o/o),  Klebsiella  spp.  in urine samples  (30.770 ), Pseudomonas  spp.in  burn.  and  surgical wounds  (25oh),  Enterobacter spp.  in  burn  wounds  (507o),  and  Acinetobacter spp.  in urine(28.57oh).  Proteus spp.  was  found  only  in burn  wounds (22.22o/o).  All AmpC f3-lactamase  producers  were sensitive  toImipenem  (100%).  Considerable  numbers of  AmpC producing  bacteria  were detected  from  wound  infection  andurinary  tract  infection  cases  which  indicate  that  AmpC is  a major threat  for  antibiotic therapy.Bangladesh  J Med  Microbiol2008;02(01):28-32DOI: http://dx.doi.org/10.3329/bjmm.v2i1.21930